Fluctuations of fresh-saline water interface and of water table induced by sea tides in unconfined aquifers. (October 2016) - Levanon, Elad; Shalev, Eyal; Yechieli, Yoseph; Gvirtzman, Haim
Highlights: We examine the effects of sea-tides on fluctuations of the fresh-saline water interface and water table in coastal aquifers. Time-lags of salinity were found to be much larger than that of the hydraulic head at the same spots along the interface. In addition, the time-lag of salinity in the fresh-saline water interface was similar to the time-lag of the water table. Tidal effect is explained by pressure wave within the saturated zone and water table attenuation due to capillary effect. The relatively-quick pressure wave propagation causes relatively-slow fluctuations of the entire fresh-water lens. Abstract: This study examines effects of tides on fluctuations of the fresh-saline water interface and the groundwater level in unconfined coastal aquifers using a two-dimensional numerical model. The time-lags of the simulated hydraulic heads and salinities fluctuations compared to sea level fluctuations are analyzed using cross-correlation analysis. The results show that both the fresh-saline water interface and the groundwater level are affected harmonically by sea tide fluctuations. However, significantly different time-lags are obtained between the hydraulic head in the deeper and upper parts of the aquifer, and between head and salinity in the fresh-saline water interface. The hydraulic head in the deeper part of the aquifer responses much faster to sea level fluctuations than in the upper part. Surprisingly, a similar difference is detected between the time-lag of the hydraulic head in the fresh-saline water interface and the time-lag of the salinity at the same location. Furthermore, the time-lag of the salinity in the fresh-saline water interface is similar to the time-lag of the water table. We suggest a comprehensive mechanism for tidal influence on the coastal groundwater system, in which two main processes act simultaneously. First, sea tide causes a pressure head wave which propagates into the saturated zone of the aquifer, governed by the diffusivity of the aquifer ( Ks /Ss ). Second, this pressure head wave is attenuated at the water table due to the unsaturated flow within the capillary fringe which occurs during groundwater level oscillations. Because the tidal forcing acts on the sea-floor boundary and the attenuation of the groundwater level due to capillary effect acts on the groundwater table, two dimensional distributions of time-lag and hydraulic head amplitude are created. The capillary effect in the unsaturated zone plays a key role not only in the water table fluctuations as shown previously, but also on the salinity fluctuations in the fresh-saline water interface. Unsaturated flow dynamics controls the actual movement of the entire fresh water body, which results in simultaneous fluctuations of the groundwater level and the fresh-saline water interface.